Antigen Loading (e.g., Glutamic Acid Decarboxylase 65) of Tolerogenic DCs (tolDCs) Reduces Their Capacity to Prevent Diabetes in the Non-Obese Diabetes (NOD)-Severe Combined Immunodeficiency Model of Adoptive Cotransfer of Diabetes As Well As in NOD Mice - Funda, David P.; Goliáš, Jaroslav; Hudcovic, Tomáš; Kozáková, Hana; Špíšek, Radek; Palová-Jelínková, Lenka (Frontiers in Immunology, 2018)
Tolerogenic dendritic cells (tolDCs) are being researched as a promising intervention strategy also in autoimmune diseases including type 1 diabetes (T1D). T1D is a T-cell mediated, organ-specific disease with several well-defined and rather specific autoantigens, i.e. proinsulin, insulin, GAD65, that have been used in animal as well as human intervention trials in attempts to achieve a more efficient, specific immunotherapy. In this study, we have tested tolerogenic DCs for their effectiveness to prevent adoptive transfer of diabetes by diabetogenic splenocytes into NOD-SCID recipients. While i.p. application of tolDCs prepared from bone marrow of prediabetic NOD mice by vitamin D2 and dexamethasone significantly reduced diabetes transfer into the NOD-SCID females, this effect was completely abolished when tolDCs were loaded with the mouse recombinant GAD65, but also with a control protein - ovalbumin (OVA). The effect was not dependent on the presence of serum in the tolDC culture. Similar results were observed in NOD mice. Removal of possible bystander APCs within the diabetogenic splenocytes by negative magnetic sorting of T cells did not alter this surprising effect. Tolerogenic DCs loaded with an immunodominant mouse GAD65 peptide also displayed diminished diabetes preventive effect. Tolerogenic DCs were characterized by surface maturation markers (CD40, CD80, CD86, MHC II) and the LPS stability test. Data from alloreactive T cell proliferation and cytokine induction assays (IFN-γ) did not reveal the differences observed in the diabetes incidence. Migration of tolDCs, tolDCs-GAD65 and tolDCs-OVA to spleen, mesenteric- and pancreatic-lymph nodes displayed similar, mucosal pattern with highest accumulation in pancreatic lymph nodes present up to 9 days after the i.p. application. These data document that mechanisms by which tolDCs operate in vivo require much better understanding for improving efficacy of this promising cell-therapy, especially in the presence of an antigen, e.g. GAD65.